Early Coastal Fiber Technology from the Caleta Vitor Archaeological Complex in Northern Chile. Issue 2 (June 2019) - Martens, Tracy; Cameron, Judith
Abstract : The marine subsistence economy of the prehistoric people of northern Chile was heavily reliant on fiber technology for the components of nets, lines, and tethers. Despite the significance and the remarkable preservation of fiber artifacts along the arid Atacama coastline, these components have received little direct attention. This case study of fiber artifacts from the Caleta Vitor archaeological complex is the first broad overview of techniques, material usage/preference, and fiber-processing conventions at a northern Chilean Archaic period site. The data presented in this paper indicate gradual change in material preferences over time, shifting from locally available vegetal fiber, which dominates the Archaic period, with small amounts of camelid fiber, to the predominance of camelid fiber in the Late Formative period. This change coincides with the appearance of more complex weaving techniques indicating participation in the previously established textile tradition proposed by Ulloa (2008) as stretching from the Azapa Valley to the Loa River. Abstract : La economía de subsistencia marina de las poblaciones prehistóricas del norte de Chile dependía, en gran medida, del trabajo de la fibra para la elaboración de redes, líneas de pesca y cuerdas. A pesar de la importancia y la notable preservación de los artefactos de fibra a lo largo de la costa árida de Atacama, estos elementos de cordelería han recibido poca atención. Este trabajo, sobre los artefactos de fibra del complejo arqueológico de Caleta Vitor, constituye la primera descripción general de la técnica, del uso/preferencia de materiales y de las convenciones sobre el procesamiento de la fibra en un sitio arqueológico del período arcaico en el norte de Chile. Asimismo, se consideran las técnicas de tejido más complejas que aparecen en el período Formativo tardío, que consolidan la tradición textil previamente establecida, propuesta por Ulloa (2008), que se extiende desde el Valle de Azapa hasta el Río Loa.